2010
DOI: 10.1007/s11033-010-0586-0
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of differentially-expressed proteins in esophageal cancer in three ethnic groups in Xinjiang

Abstract: The Objective is to identify candidate biomarkers for Squamous cell carcinoma (ESCC) in three ethnics in Xinjiang as well as reveal molecular mechanism. Proteins from 15 pairs of ESCC and matching adjacent normal esophageal tissues (five pairs in each ethnic of Kazakh, Uygur and Han) were separated by 2-DE and differentially proteins were identified by matrix-assisted laser desorption/ionization time-of-flight MS. After identified by Mascot database, some of interesting proteins were confirmed in the other 175… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 19 publications
3
45
0
Order By: Relevance
“…The commonly identified proteins with the same change direction included alpha enolase, TPM, tubulin, prohibitin and PRX2. Although the prevalence of ESCC in Xinjiang is comparable to Linzhou, the protein signatures were unique to sample origin, indicative of more important roles of environmental, ethnic or hereditary factors in the carcinogenesis of ESCC [Liu et al, 2011]. It seems that hsp27 was a general molecular events involved in ESCC since four out of five studies observed down-expression in ESCC except ours.…”
Section: Two-dimensional Electrophoresis-based Proteomic Findings Of mentioning
confidence: 62%
See 3 more Smart Citations
“…The commonly identified proteins with the same change direction included alpha enolase, TPM, tubulin, prohibitin and PRX2. Although the prevalence of ESCC in Xinjiang is comparable to Linzhou, the protein signatures were unique to sample origin, indicative of more important roles of environmental, ethnic or hereditary factors in the carcinogenesis of ESCC [Liu et al, 2011]. It seems that hsp27 was a general molecular events involved in ESCC since four out of five studies observed down-expression in ESCC except ours.…”
Section: Two-dimensional Electrophoresis-based Proteomic Findings Of mentioning
confidence: 62%
“…Our findings indicate that MIF may play crucial roles in malignant transformation of pathogenesis of EC and MIF could become a potential biomarker for high-risk population screening, assessment of therapeutic efficiency, prognostic evaluation, and molecular targets of developing novel therapeutic regimen as well. In addition of our proteomic results in ESCC, several other reports have looked at the clinical value of potential biomarkers, including cytokeratin 14, Annexin I, SCCA1/2, calgulanulin B and HSP 60, alpha-actinin 4 and 67 kDa laminin receptor, cathepsin D and PKM2, periplakin, calreticulin and GRP78, galectin-7, anti-CD25B antibody [Dong et al, 2010;Du et al, 2007;Fu et al, 2007;Hatakeyama et al, 2006;Liu et al, 2011;Nishimori et al, 2006;Zhu et al, 2010]. Nevertheless, further extensive studies are still necessary to determine the clinical utility of the identified proteins in tumorigenesis and progression of ESCC.…”
Section: Protein Name T/n Ratio Functions References Prohibitinmentioning
confidence: 88%
See 2 more Smart Citations
“…There, minority patients occupy a great proportion of all EC patients, among which the highest incidence is found in Kazakh population and the second in Uigurs (Zhou et al, 2009). Minority EC patients are different from Han patients in living habits and constitution, and the pathogenesis of EC among minorities is also somewhat different from that among Hans (Liu et al, 2011). In China, esophageal squamous cell carcinoma is the major pathological form of EC and esophageal adenocarcinoma only accounts for 0.4% of EC cases (Zou et al, 2002).…”
Section: Introductionmentioning
confidence: 99%